Análisis del riesgo financiero en los microcréditos de las cooperativas del segmento 3 de la ciudad de Latacunga en el periodo 2013-2018. - Caillagua Bonilla, Ericka Dayana (2019)
This research project refers to the financial risk in the microcredits Segment 3 banks of Latacunga city, as well as in the analysis of the financial soundness of these companies, with the purpose of establishing a supervision method and early warning that allows these organizations and the financial system of the popular and solidary sector to take timely decisions and appropriate measures in order to avoid in future potential closures and forced liquidations. In the first instance, for the development of this research, the referential theoretical framework that supported the elements of risk in the banks and the applied methodology was analyzed, through an exploratory research. Then a refined database of the financial statements of the banks of segment 3 of Latacunga city was obtained from January 2017 to August 2018, information that was used to review the impact of the risk in the microcredit portfolio through indicators static loans, and later establish the institutional solidity and solvency through the CAMELS Model (capital protection (C), asset quality (A), management capacity (M), utility solidity (E) , the liquidity risk (L) and the market risk (S)), using qualitative and quantitative methods in this case. Finally, with the obtained results, an analysis and interpretation was made which allowed to know that there was an improvement in the levels of delinquency in the Sumak Kawsay bank, and a deterioration in the Educadores Primarios of Cotopaxi bank. This was confirmed through the CAMELS model, which in the period under study, the Sumak Kawsay bank is the most solid and the Educadores Primarios of Cotopaxi bank is the institution which should concentrate its efforts on improving some components of its financial structure.